Long-term Outcome following Percutaneous Intervention of Intra-stent Coronary Occlusion and Evaluating the Different Treatment Modalities. (June 2021) - Basavarajaiah, Sandeep; Mitomo, Satoru; Nakamura, Sunao; Sharma, Vinoda; Mohammed, Ishaq; Watanabe, Yusuke; Ouchi, Toru; Bhatia, Gurbir; Ment, Jerome; Athukorala, Sampath; Pitt, Michael; Pulikal, George; et al.
Highlights: Limited data on intra-stent CTO. We explored the long-term outcomes in patients undergoing PCI to intra-stent CTO. Acceptable rates of hard endpoints (cardiac death; 5.8%, TVMI; 4%). High rates of TLR (45.6%). PCI should only be undertaken if symptomatic or if there is inducible ischaemia. If PCI is undertaken, DCB and DES should be considered over POBA. Abstract: Background: Angioplasty for ISR remains a challenge with relatively high rates of recurrence. Although there is a plethora of data on ISR, there is relatively less data on intra-stent-CTO. In this study, we explore the long-term clinical outcomes following angioplasty to intra-stent CTO and study the differences in clinical outcomes between three treatment-arms: POBA vs. DES vs. DCB. Methods and results: We evaluated all patients who underwent PCI to intra-stent CTO between 2011 and 2017. The endpoints used were: cardiac-death, TVMI, TLR, TVR, and MACE. During the study period, 403-patients with a mean age of 69.2 years had successful PCI to intra-stent CTO. 50% were diabetic, 38% had CKD and 32% had left ventricular dysfunction. 93% of cases were stable angina. 22% (n = 88) received only POBA, 28% (n = 113) received DCB and 50% (n = 202) received DES. During the median follow-up of 48-months, cardiac-death occurred in 5.8% (n = 23), TVMI in 4% (n = 16), TLR in 45.6% (n = 182), TVR in 48.7% (n = 194) and MACE of 46%. There were no differences in the hard endpoints between the 3treatment arms. However, the TLR and overall MACE were better in DCB and DES-groups as compared to POBA (TLR: 33%vs.42%vs.49%; p = 0.06); MACE (34% vs. 45% vs. 52%; p = 0.05). Conclusion: This is the first study that has focussed on the outcomes following angioplasty to intra-stent CTOs with a very long-term follow-up. The hard endpoints were low, although the TLR rates were high. In regards to treatment strategy, the DCB and DES provide relatively better outcomes than POBA.